Journal Economics, business & accountancy : ANALYSIS OF THE FACTORS DETERMINING THE AUDIT FEE - Kusharyanti (PPPM Perbanas, 2013)
There are some factors considered to have an effect on the audit fee amount. These are importantfor the researchers to analyze. This research aimed to test the determinants of auditfee in companies that are listed on Indonesian Stock Exchange (ISE). The samples of thisstudy were 60 companies in period 2010-2011